EKSISTENSI KONFLIK KELUARGA DAN KELOMPOK SOSIAL DALAM NOVEL RENCANA BESAR UNTUK MATI DENGAN TENANG KARYA WISNU SURYANING ADJI - Dwi Leoni, Tessa; Arya Prapanca, Octavino (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to describe the forms of social conflict contained in the novel "Plan Besar untuk Mati dengan Tenang" by Wisnu Suryaning Adji. The method applied in this study is content analysis. The researcher acts as the main instrument supported by research aids. The research data are in the form of quotations sourced from the novel "Plan Besar untuk Mati dengan Tenang". Data collection was carried out through documentation techniques or literature studies, while testing the validity of the data used source triangulation techniques. The results of the study show the existence of two forms of social conflict, namely (1) family conflict in social roles characterized by differences of opinion among family members and (2) conflict between social groups shown through conflicting views within a group. Based on the results of data processing, 10 data were found that reflect both forms of conflict, with details of 5 data including family conflict in social roles and 5 other data including conflict between social groups.